Discrimination based on gender identity and decision-making regarding HIV/STI-protected sex, a cross-sectional study among trans and non-binary people in Germany - Mario Martín-Sánchez; Kathleen Pöge; Alexander Hahne; Jonas Hamm; Viviane Bremer; Uwe Koppe; The TASG-study group (BMC, 2024)
Abstract Background Trans and non-binary people are often discriminated against. Discrimination has a negative impact on health and may affect sexual health and behavior. We explored the relationship between discrimination based on gender identity and the perceived ability to make decisions about their sex life to feel as protected as desired from HIV and sexually transmitted infections (STI) among trans and non-binary people in Germany. Secondarily, we assessed whether feeling unable of making HIV/STI-protected sex decisions was associated with behaviors related to increased HIV/STI risk. Methods We conducted a cross-sectional study using data from the Sexual Health and HIV/STI in Trans and Non-Binary Communities (TASG) survey conducted online between March-July 2022 among trans and/or non-binary people aged 18 years and older living in Germany. We described the prevalence of frequent discrimination based on gender identity. We calculated prevalence ratios (PR) with 95% confidence intervals (95% CI) for the associations between frequent experienced discrimination based on gender identity and feeling unable of making HIV/STI-protected sex decisions, and between feeling unable of making HIV/STI-protected sex decisions and behaviors related to increased HIV/STI risk. Results Among 3077 participants, 22% reported frequent discrimination based on gender identity. Participants experiencing such discrimination reported 1.4 times more often to feel unable to make HIV/STI-protected sex decisions (PR 1.4, 95% CI 1.1-1.8). This perceived inability was associated with increased prevalence of sex under drug influence (PR 2.9, 95% CI 2.3-3.7) and condomless penetrative sex with multiple partners without PrEP (PR 2.0, 95% CI 1.4-2.9). Conclusion Feeling unable to make decisions to feel protected from HIV/STI among trans and non-binary people was associated with both frequent discrimination and behaviors that increase the HIV/STI risk. Strategies for empowering trans and non-binary people to assert their sexual decision-making needs should be explored.